STUDY OF MOTION RESPONSES OF THE H-TYPE FLOATING BREAKWATER - Awg Yusuf, Awang Khairul Amzar (Universiti Teknologi PETRONAS, 2013)
This study focuses on the hydrodynamics behavior of a floating breakwater with taut leg mooring configuration. The aim of the study is to understand the motion responses of the H-type floating breakwater and the effects of the mooring system on the motion responses of the floating breakwater. This study focuses only on the heave, surge and pitch movements, whilst the other motion responses were restricted. In order to quantify the motion responses of the floating breakwater, the Response Amplitude Operator (RAO) was utilized in the study. The RAO values for heave, surge and pitch obtained in the study will provide an insight on the extent of the movement of the H-type floating breakwater subjected to various wave conditions. The results show that the motion responses of the floating breakwater are heavily affected by the breakwater’s drafts and the wave period. The recorded RAO values show that the motion responses of heave and surge decreased with an increase of the breakwater draft. However, as for the case of pitch RAOs, no specific pattern can be recorded; a clear indication that the pitch responses are less significant as far as changing the drafts is concerned. All of the RAO values of the heave, surge and pitch are rather sensitive to the change of wave period, as the RAOs vary significantly with the increasing wave period. The motion responses for all the heave, surge and pitch also show significant differences when subjected to different wave steepness, with lower RAO values recorded milder wave steepness (H/L = 0.04). However, the RAOs are less sensitive at higher wave steepness (H/L = 0.06 and H/L = 0.08) and the effect are rather scarce. The RAO’s patterns for both regular and random waves are almost identical; with the RAOs for regular waves tend to produce larger values as compared to random waves.